Geochemical and microbial community determinants of reductive dechlorination at a site biostimulated with glycerol. (6th October 2016) - Atashgahi, Siavash; Lu, Yue; Zheng, Ying; Saccenti, Edoardo; Suarez‐Diez, Maria; Ramiro‐Garcia, Javier; Eisenmann, Heinrich; Elsner, Martin; J.M. Stams, Alfons; Springael, Dirk; Dejonghe, Winnie; Smidt, Hauke
Summary: Biostimulation is widely used to enhance reductive dechlorination of chlorinated ethenes in contaminated aquifers. However, the knowledge on corresponding biogeochemical responses is limited. In this study, glycerol was injected in an aquifer contaminated with cis ‐dichloroethene (cDCE), and geochemical and microbial shifts were followed for 265 days. Consistent with anoxic conditions and sulfate reduction after biostimulation, MiSeq 16S rRNA gene sequencing revealed temporarily increased relative abundance of Firmicutes, Bacteriodetes and sulfate reducing Deltaproteobacteria. In line with 13 C cDCE enrichment and increased Dehalococcoides mccartyi ( Dcm ) numbers, dechlorination was observed toward the end of the field experiment, albeit being incomplete with accumulation of vinyl chloride. This was concurrent with (i) decreased concentrations of dissolved organic carbon (DOC), reduced relative abundances of fermenting and sulfate reducing bacteria that have been suggested to promote Dcm growth by providing electron donor (H2 ) and essential corrinoid cofactors, (ii) increased sulfate concentration and increased relative abundance of Epsilonproteobacteria and Deferribacteres as putative oxidizers of reduced sulfur compounds. Strong correlations of DOC, relative abundance of fermenters and sulfate reducers, and dechlorination imply the importance of syntrophic interactions to sustain robust dechlorination. Tracking microbial and environmental parameters that promote/preclude enhanced reductive dechlorination should aid development of sustainable bioremediation strategies.